2009
DOI: 10.1007/s00520-008-0575-1
|View full text |Cite
|
Sign up to set email alerts
|

The existential experiences of receiving soft tissue massage in palliative home care—an intervention

Abstract: Soft tissue massage appears to be an appreciated source of support to dying patients in palliative home care. The method is easy to comprehend and relatively short (25 min) which may imply that it is a suitable complement in nursing care for this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
4
30
0
1
Order By: Relevance
“…Qualitative data have been published for a number of body awareness-enhancing approaches including body awareness therapy as a form of physical therapy[19,28,58,59], qigong and body scan[60], massage[61], breath therapy[18], body-oriented psychotherapy[4], and Rosen Method Bodywork[62]. The data were collected in patients with chronic musculoskeletal pain conditions[18,19,28,59,62], cancer[58,61], sexual abuse PTSD[4] and by interviewing a qigong master[60]. Each of these studies confirms several of the points that emerged in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative data have been published for a number of body awareness-enhancing approaches including body awareness therapy as a form of physical therapy[19,28,58,59], qigong and body scan[60], massage[61], breath therapy[18], body-oriented psychotherapy[4], and Rosen Method Bodywork[62]. The data were collected in patients with chronic musculoskeletal pain conditions[18,19,28,59,62], cancer[58,61], sexual abuse PTSD[4] and by interviewing a qigong master[60]. Each of these studies confirms several of the points that emerged in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, the term TM is used to cover different forms of light massage involving the skin. These forms of massage are characterized by gentle touches of the skin involving light pressure effleurage and long, calm stroking movements intended to increase the well-being [ 48 ], pleasure [ 49 ] and relaxation [ 35 ] of the recipients.…”
Section: Methodsmentioning
confidence: 99%
“…Billhult et al (2009) evaluated the effects of light massage (0·0090 kg/cm 2 pressure) on physiological outcome parameters, and concluded that light massage may have short-term effects on systolic blood pressure (SBP) and heart rate. Other studies of massage described as 'light', 'tactile', 'soft', or 'gentle' reported altered emotions after massage treatments (Andersson et al, 2009;Cronfalk et al, 2009;Henricson et al, 2009). The next step after evaluating existing evidence about the intervention was to identify or develop theories about how the intervention works.…”
Section: Developing a Complex Interventionmentioning
confidence: 99%